2012
DOI: 10.1007/s10531-012-0233-2
|View full text |Cite
|
Sign up to set email alerts
|

Fauna data integration and species distribution modelling as two major advantages of geoinformatics-based phytobiodiversity study in today’s fast changing climate

Abstract: The development and growth of geospatial techniques offer many advantages and challenges to the study of biodiversity, especially in the present era of climate change.We are now at the beginning of the international decade for biodiversity and by the time we travel through the decade, there would be sea-changes in the measurement and monitoring approaches, database management options, and inter-linked studies on biodiversity. With the onset of geoinformatics techniques comprising remote sensing, global positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Several global scale initiatives have been started to compile the vast biodiversity datasets held in museums and herbaria, publications or data resulting from intensive field surveys e.g., GBIF, EOL (Franklin 2009). The increased amount of biodiversity data available is accompanied by progress in computation that allows not only the proper management of data (Matin et al 2012) but also its advanced and precise analysis (Reese et al 2005). Basic knowledge of the species distributions within a region is required for a proper management of biodiversity, e.g., to predict species extinction under habitat loss, to understand the potential impacts of climate change on biodiversity, to prioritize conservation efforts and design conservation areas (Margules and Pressey 2000, Primack 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several global scale initiatives have been started to compile the vast biodiversity datasets held in museums and herbaria, publications or data resulting from intensive field surveys e.g., GBIF, EOL (Franklin 2009). The increased amount of biodiversity data available is accompanied by progress in computation that allows not only the proper management of data (Matin et al 2012) but also its advanced and precise analysis (Reese et al 2005). Basic knowledge of the species distributions within a region is required for a proper management of biodiversity, e.g., to predict species extinction under habitat loss, to understand the potential impacts of climate change on biodiversity, to prioritize conservation efforts and design conservation areas (Margules and Pressey 2000, Primack 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A class-wise comparison was carried out to estimate the changes in the area statistics during the period 1975-2010. The mapping accuracy was accessed using 1509 sample plots gathered through field sampling during the biodiversity characterization at landscape level project using a sample size of 20 m×20 m for trees, 5 m×5 m for shrubs and 1 m×1 m for herbs (Matin et al, 2012).…”
Section: Forest Cover Land Use Mappingmentioning
confidence: 99%
“…Species distribution models are static and probabilistic in nature as they statistically relate the geographical distribution of species or communities to their present environment. Matin et al (2012) utilized the GPS-based location information on Medicago sativa and Plantago annua to simulate their potential distribution in the year 2020 (SRES A1B scenario, IPCC) using the Maxent model in part of Ladakh Himalaya. The model suggested that the distribution of both the species would tend to move in the direction of shorter cold seasons.…”
Section: Overviewmentioning
confidence: 99%
“…Matin et al (2012) demonstrated a method to integrate the faunal component in a recently completed nationwide biodiversity study in India using the plants alone (Behera and Roy 2010). The study highlights the potential contribution of geoinformatics to biodiversity assessments .…”
Section: Overviewmentioning
confidence: 99%